Impact of m6A demethylase (ALKBH5, FTO) genetic polymorphism and expression levels on the development of pulmonary tuberculosis - Zhang, Tian-Ping; Li, Rui; Wang, Li-Jun; Li, Hong-Miao (Frontiers in Cellular and Infection Microbiology, 2022)
Objective The m6A methylation was involved in the pathogenesis of pulmonary tuberculosis (PTB), and our study aimed to reveal the potential association of m6A demethylase (ALKBH5, FTO) genes variation, expression levels and PTB. Methods Eight SNPs (ALKBH5 gene rs8400, rs9913266, rs12936694, rs4925144 and FTO gene rs6499640, rs8047395, rs1121980, rs9939609) were selected for genotyping by SNPscan technique in 449 PTB patients and 463 healthy controls. Results The mRNA expression levels of ALKBH5, FTO were detected by qRT-PCR. There were no significant differences in genotype, allele distributions of all SNPs between PTB patients and healthy controls. Haplotype analysis demonstrated that the frequency of FTO gene GAAA haplotype was significantly reduced in PTB patients when compared to controls. ALKBH5 rs8400 AA genotype, A allele frequencies were associated with the decreased risk of sputum smear-positive, while AA genotype frequency was related to the increased risk of hypoproteinemia in PTB patients. In addition, rs9913266 variant was linked to the occurrence of drug-induced liver injury, sputum smear-positive, and rs4925144 variant was associated with leukopenia among PTB patients. In FTO gene, rs8047395 GG genotype and G allele frequencies were significantly higher in the PTB patients with drug resistance than that in the PTB patients without drug resistance. The ALKBH5, FTO expression levels were significantly decreased in PTB patients in comparison to controls. Moreover, ALKBH5 level was increased in PTB patients with drug resistance, and FTO level was decreased in PTB patients with sputum smear-positive. Conclusion FTO gene polymorphisms might be associated with PTB susceptibility, and ALKBH5, FTO levels were decreased in PTB patients, suggesting that these m6A demethylase played important roles in PTB.